EVALUATION OF THE COPULATIVE FUNCTION IN PATIENTS AFFECTED BY TRANSRETRAL AND ENDOVIDEOSURGERIC INTERVENTIONS FOR BENIGN PROSTATIC HYPERPLASIA - S. V. Popov; I. N. Orlov; T. M. Topuzov; E. A. Grin’; P. S. Kyzlasov (Вестник урологии, 2017)
Relevance. Absence of studies on the effect of various transurethral and endovideosurgical methods (EVS) of operative treatment of benign prostatic hyperplasia (BPH) on the state of the copulative function, which includes the analysis of its main components within the framework of a single study.Aim. Study the effect of the above methods of correction of BPH on the state of the main components of the copulatory function.Materials and methods. Analysis of the results of surgical treatment of 220 patients with BPH who underwent transurethral resection-TUR (n = 80), transurethral enucleation with bipolar TUEB (n = 51), holmium laser enucleation of the prostate-HoLEP (n = 43), and endovideosurgical adenomectomy- EVS AE (n = 46). The study included: the international index of erectile function, the scale of the male copulative function score, the score of the questionnaire for the aging males symptoms (AMS), the quality of life index for erectile dysfunction, the degree of bulbocavernosis reflex, the testosterone fraction and the globulin binding sex hormones (GBSG). Patients were examined before the operation, and also after 3 and 6 months. Results. The number of patients with decreased libido was significantly lower in the TUR groups (from 56.3% to 53, 75% (3 months) and 47.5% (6 months)) and EVS AE (from 43.4% to 39.1% (3 months) and 32.6% (6 months)). A decrease in the specific gravity of ED in the postoperative period (group TUR BPH (from 50% to 45% (3 months) and 42.5% (6 months), group TUEB (from 52.9% to 51.5% (3 months) and 49.2% ( 6 months), the HoLEP group (from 69% to 66.6% (3 months) and 60% (6 months) and EVS AE (from 68.75% to 65% (3 months) and 62.5% (6 months)) with a parallel improvement in severity (from 40% to 37.5% (3 months), 35% (6 months), and EVS AE (from 31.25% to 28.3% (3 months) and 25% (6 months)), the number of patients with hyporgasmia. With respect to retrograde ejaculation, there was a decrease in the incidence of its occurrence in the TUR group (from 25% to 22.5% (3 months) and 19.6% (6 months) and EVS AE (from 18.75% to 15.3% (3 months) and 12% (6 months.) In addition, there was no statistically significant difference in the level of testosterone and GBSG fractions in the pre- and postoperative period (3 months), but when monitoring at a more distant time (6 months), there was a tendency to increase testosterone fractions with a parallel decrease in the concentration of GBSG.Conclusions. Surgical correction of BPH with endoscopic and EVS methods has a positive effect on the copulatory function and hormonal status, which is especially pronounced in the groups of TUR BPH and EVS AE.